The analysis of foreign market entry strategies on the basis of different cultural backgrounds and environments: a qualitative study characterising the differences and similarities of Brazilian and European firms - Schlechtriem, Maximilian (2016)
Moving into a new and foreign market can be challenging, especially when such market has a different culture and working environment in comparison to the home market. Thus, it is of utter importance to adjust a company’s strategy to the new market conditions. Currently, there are no concrete guidelines of what aspects are most important when moving from a developing market such as Brazil into a more sophisticated market like Europe, or vice versa. The present study will examine two companies from the same industry, but with different cultural backgrounds and its strategic similarities and differences for operating in multiple international markets. The data was collected via semi-structured interviews with the Chief Executive Officers (CEOs’) from both companies, using an interview guideline that is based on three different theoretical frameworks. The aim is to give recommendations to these two industries of how to efficiently use existing theoretical frameworks and which aspects are most significant when moving into a new market while keeping in mind a company’s size and background.